The Strategic Contribution of Leadership and Empowerment to Organizational Resilience - Agus Salim Dasuki; Soewarto Hardhienata; Nandang Hidayat (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Rapid technological disruption and increasing uncertainty in the higher education landscape demand that institutions strengthen their organizational resilience through effective leadership, knowledge management, adaptive culture, and empowerment. This study aims to formulate strategies to enhance organizational resilience by examining the direct and indirect effects of visionary leadership as an independent variable and knowledge management, organizational culture, and empowerment as mediating variables. Using a quantitative approach, data were collected from 191 respondents across ten private universities in East Jakarta through multistage random sampling. The study employed survey methods, path analysis, and SITOREM analysis to identify key determinants of resilience. The findings reveal that visionary leadership, knowledge management, organizational culture, and empowerment each have a significant positive influence on organizational resilience. Furthermore, visionary leadership significantly affects knowledge management, organizational culture, and empowerment, which in turn mediate its impact on resilience. These results underscore the importance of integrated leadership practices and adaptive organizational systems in fostering institutional strength amid disruption. The implications of this study highlight the need for policymakers, particularly the Ministry of Education, Culture, Research, and Technology and LLDIKTI Region 3, to support resilience-oriented leadership development and institutional strategies to enhance the quality and sustainability of higher education in Indonesia.